2019
DOI: 10.1108/jmlc-01-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Aligning financial inclusion and financial integrity

Abstract: Purpose This study aims to consider the anti-money laundering/combating of financing of terrorism (AML/CFT) regime that applies to microfinance institutions (MFIs) and microfinance programmes and projects (MFPs) in Vietnam to identify ways in which to improve the alignment between financial inclusion and financial integrity objectives in relation to this sector. Design/methodology/approach This doctrinal study is informed by the Financial Action Task Force mutual evaluation methodology. Findings The AML/CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…The results reinforce a technological opportunity to simplify the KYC and AML procedures that currently limit underserved populations' access to banking services. Such simplifications make sense as these populations are predominantly not dangerous clients and simply lack the skills to comply with such requirements (Tran and De Koker 2019) or the availability or willingness to provide data (Macchiavello and Siri 2022). From a technological standpoint, one way to do this is by providing layered-permission access solutions through innovative APIs, as suggested by Romanova et al (2018) in relation to the security and privacy risks related to OB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reinforce a technological opportunity to simplify the KYC and AML procedures that currently limit underserved populations' access to banking services. Such simplifications make sense as these populations are predominantly not dangerous clients and simply lack the skills to comply with such requirements (Tran and De Koker 2019) or the availability or willingness to provide data (Macchiavello and Siri 2022). From a technological standpoint, one way to do this is by providing layered-permission access solutions through innovative APIs, as suggested by Romanova et al (2018) in relation to the security and privacy risks related to OB.…”
Section: Discussionmentioning
confidence: 99%
“…Research on microfinance in Vietnam has shown the necessity to simplify anti-money laundering (AML) and KYC procedures for two reasons (Tran and De Koker 2019). First, their customers' activities are unlikely to be associated with terrorism or money laundering.…”
Section: Challengesmentioning
confidence: 99%
“…(Babajide et al, 2017;Değermen Erenkol et al, 2015), meningkatkan kesetaraan gender. Owusu-Danso (2015) serta meningkatkan inklusi keuangan (Ginanjar & Kassim, 2021) mampu malayani semua segmen sosial sehingga kemiskinan bisa lebih mudah diperangi (Bishwakarma, 2017;Ginanjar, 2015;Othman, 2015;Sarker, 2013;Tran & De Koker, 2019) serta meningkatkan literasi digital (Mushtaq & Bruneau, 2019).…”
Section: Pendahuluanunclassified
“…Evans (2018) finds that factors such as capital formation, bank credit, broad money, population growth, remittances, interest rate and regulatory quality significantly influence the level of financial inclusion. Tran and De Koker (2019) argue that strong anti-money laundering (AML) and combating terrorism financing (CFT) regulatory frameworks for microfinance institutions can help to align financial inclusion policy objectives with financial integrity in the activities of microfinance institutions. Ozili (2020b) in a recent review of literature, finds that financial inclusion affects, and is influenced by, the level of financial innovation, poverty levels, the stability of the financial sector, the state of the economy, financial literacy, and regulatory frameworks which differ across countries.…”
Section: The Policy Literaturementioning
confidence: 99%